A Single-Layer PDMS Chamber for On-Chip Bacteria Culture - Pablo Morales Navarrete; Jie Yuan (Micromachines, 2020)
On-chip cell culture devices have been actively developed for both mammalian cells and bacteria. Most designs are based on PDMS multi-layer microfluidic valves, which require complicated fabrication and operation. In this work, single-layer PDMS microfluidic valves are introduced in the design of an on-chip culture chamber for E. coli bacteria. To enable the constant flow of culturing medium, we have developed a (semi-)always-closed single-layer microfluidic valve. As a result, the growth chamber can culture bacteria over long duration. The device is applied for the whole-cell detection of heavy metal ions with genetically modified E. coli. The platform is tested with culturing period of 3 h. It is found to achieve a limit-of-detection (LoD) of 44.8 ppb for Cadmium ions.